Prospects of Quality Research and Evaluation of Education in Bangladesh - Rana, Md. Masud; Gomes, Kamol; Jahan, Rounak; Khondoker, Md. Fahmid Uddin; Hossain, Md. Iqbal; Hoque, AKM Fazlul (Journal of Science Foundation, 2020)
Education is the backbone of a nation. Only a splendid mentor can provide the educational system for the country by using his or her wisdom. Teachers are obligate to universal and quality education for all; they are central to shaping the minds and attitudes of the coming generations to deal with new global challenges and opportunities. In many countries, the quality of education is undermined by a severe deficit of teachers. The shortage of qualified teachers is hampering efforts in many countries to achieve quality education for all. Teachers are often lacking of good resources such as teaching materials, textbooks, proper training etc. The quality of teaching is cardinal to proper learning outcomes. This implies an education system that attracts and retains a magnificent teaching staff and supports teachers in the classroom, as well as in their continued professional development. Higher education with research is one of the important parts of the education system. The key aims of higher education are to generate the new knowledge, explore research works on different social and development issues, anticipate the needs of the economy and prepare highly skilled workers. In these contexts, higher education should be standard, welfare and sustainable development oriented. The present paper intends to analyze the higher education system of Bangladesh in the light of diversity, quality and accessibility. Journal of Science Foundation 2019;17(2):46-53